2019
DOI: 10.3389/fmicb.2019.01738
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Strains Differentially Shift the Genetic Structure of Indigenous Soil Populations of Aspergillus flavus

Abstract: Biocontrol using non-aflatoxigenic strains of Aspergillus flavus has the greatest potential to mitigate aflatoxin contamination in agricultural produce. However, factors that influence the efficacy of biocontrol agents in reducing aflatoxin accumulation under field conditions are not well-understood. Shifts in the genetic structure of indigenous soil populations of A. flavus following application of biocontrol products Afla-Guard and AF36 were investigated to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 79 publications
2
27
0
Order By: Relevance
“…The places of their isolation may reflect respective ecological niches preferable for growth and development. A recent report on the application of AF36 and NRRL21882 to maize fields in Alabama, Georgia and North Carolina, where AF36 is not registered for use, shows that A. flavus individuals belonging to the 21882‐type classified by multilocus haplotypes are the most dominant in the soils, but AF36‐type individuals are recovered only in very low frequencies (Lewis et al ). Although NRRL21882 also can be found in above‐ground tissues, consistent with the observed niche adaption NRRL21882‐type isolates have been found in soils of many southern states in the United States, and it is estimated that 16·3% of the total A. flavus isolates collected from those soil samples belong to this type (Horn and Dorner ; Chang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The places of their isolation may reflect respective ecological niches preferable for growth and development. A recent report on the application of AF36 and NRRL21882 to maize fields in Alabama, Georgia and North Carolina, where AF36 is not registered for use, shows that A. flavus individuals belonging to the 21882‐type classified by multilocus haplotypes are the most dominant in the soils, but AF36‐type individuals are recovered only in very low frequencies (Lewis et al ). Although NRRL21882 also can be found in above‐ground tissues, consistent with the observed niche adaption NRRL21882‐type isolates have been found in soils of many southern states in the United States, and it is estimated that 16·3% of the total A. flavus isolates collected from those soil samples belong to this type (Horn and Dorner ; Chang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, high genotypic diversity is suggestive of some recombination between lineages ( 18 , 19 ). Recently, mating between A. flavus isolates has been achieved in field experiments ( 20 , 21 ) using extremely high population densities that better reflect artificial biocontrol conditions; i.e., higher densities of nonaflatoxigenic A. flavus propagules have been applied to agricultural fields than would normally exist under agricultural or natural conditions. The idea that A. flavus may be predominantly sexual ( 21 ) is difficult to reconcile with a large body of evidence about the predominantly asexual nature of this fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mating between A. flavus isolates has been achieved in field experiments ( 20 , 21 ) using extremely high population densities that better reflect artificial biocontrol conditions; i.e., higher densities of nonaflatoxigenic A. flavus propagules have been applied to agricultural fields than would normally exist under agricultural or natural conditions. The idea that A. flavus may be predominantly sexual ( 21 ) is difficult to reconcile with a large body of evidence about the predominantly asexual nature of this fungus. Importantly, these field studies occurred on very short timelines and thus do not capture whether the fitness of recombinant progeny is reduced by the disassociation of coadapted traits (i.e., recombination load), and thus sexual reproduction makes little contribution to the overall population.…”
Section: Introductionmentioning
confidence: 99%
“…Hruska et al [ 33 ] demonstrated via competitive exclusion that the decreased AF level was positively correlated to the low population of the toxigenic A. flavus under treatment, where the biocontrol A. flavus strain showed increased propagation and colonization. Recent studies demonstrated that biocontrol non-aflatoxigenic strains reduced AF concentrations in treated crops by more than 80% under both field and storage conditions [ 34 , 35 , 36 ]. In Argentina, a native atoxigenic A. flavus strain showed a remarkable biocontrol potential on peanuts, and the pre-harvest application of the biocontrol agent had a carry-over effect and protected peanuts under storage conditions [ 37 ].…”
Section: Pre-harvest Biocontrolmentioning
confidence: 99%